(untitled) (Fiep Bulletin - online, 2013)
The Temporomandibular Disorder (TMD) is a heterogeneous syndrome consisting of symptoms and relevant dental and neurotology, and how it causes dysfunction of the temporomandibular joint (TMJ). It is estimated that 50-70% of the population shows signs of dysfunction at some stage during their life, so that there is predominance in women aged 20 to 40 years. The relationship with TMD headache is very narrow, and it is known that there is a greater prevalence in people with TMD. The aim was to assess the prevalence of TMD associated with headache in university courses in Physical Education and Physiotherapy and check the difference in range of motion of the TMJ in TMD patients and asymptomatic. The sample consisted of 72 individuals, distributed in TMD group (n = 52), and control group (n = 20). Individuals responded to the questionnaire for distribution groups Fonseca and after, there was a maximum mandibular opening (mm) to overlap the horizontal (mm) between the incisors of both groups. There was significant difference between the measurement of maximum mandibular opening between the two groups (p = 0.001) and a high frequency of headache in individuals TMD group (69%). In future studies we suggest the use of more accurate tools for diagnosis of TMD and recruitment of a sample with proportions of similar age and gender between groups.